QOLP-08. UTILIZING STAKEHOLDER ENGAGEMENT TO DEVELOP A MINDFULNESS-BASED INTERVENTION FOR PATIENTS WITH GLIOBLASTOMA (GBM) AND THEIR CAREGIVERS. (9th November 2020) - Donovan, Laura; Driver, Aurelia; Wilkie, Martha; Morris, Jessica; Hillyer, Grace
Abstract: BACKGROUND: Patients with GBM and their caregivers report impaired quality of life (QOL). Distress, fatigue and anxiety are common. Mindfulness-based interventions (MBIs) can help reduce anxiety and depression and improve QOL in patients with chronic diseases and other types of cancer, but have not been well studied in patients with brain tumors and their caregivers. The feasibility and acceptability of an MBI in this population is unknown. METHODS: Using the Consolidated Framework for Implementation Research (CFIR), we developed a 15-minute survey for patients with brain tumors and their caregivers to assess attitudes and beliefs toward a MBI. As this study is formative, we chose to assess select domains including intervention characteristics, characteristics of individuals (knowledge and beliefs), and the outer setting (patient needs and resources). Questions were adapted from the literature to reflect constructs from each domain or created by the authors. The survey was published using Qualtrics, an online survey platform. We partnered with OurBrainBank to distribute the survey to key stakeholders using social media platforms. OurBrainBank is a patient-led movement centered around a symptom-tracking app for patients and carers, participation in patient-driven research, improved access to clinical trials, and patient advocacy. RESULTS: The survey was published on 5/29/20. In one week, we received 14 responses. 7/14 identified as having a brain tumor or being the primary caregiver for someone with a brain tumor. Of these, 5/7 indicated they would be possibly or definitely interested in participating in a research study testing a MBI. Over the next 5 months, we anticipate 200 people will complete the survey. We will analyze the results using descriptive statistics. DISCUSSION: Technology can aid in stakeholder engagement which is critical to intervention development. Results from this survey will be used to develop a MBI tailored to patients with GBM and their caregivers.